Global trends and research status in ankylosing spondylitis clinical trials: a bibliometric analysis of the last 20 years - Zhang, Wenhui; Li, Meng; Li, Xuhao; Wang, Xingxin; Liu, Yuanxiang; Yang, Jiguo (Frontiers in Immunology, 2024)
Background: Ankylosing spondylitis (AS) is a rheumatic and autoimmune disease associated with a chronic inflammatory response, mainly characterized by pain, stiffness, or limited mobility of the spine and sacroiliac joints. Severe symptoms can lead to joint deformity, destruction, and even lifelong disability, causing a serious burden on families and society as a whole. A large number of clinical studies have been published on AS over the past 20 years. This study aimed to summarize the current research status and global trends relating to AS clinical trials through a bibliometric analysis. Methods: The Web of Science Core Collection database was searched for publications related to AS clinical trials published between January 2003 and June 2023. Bibliometric analysis and web visualization were performed using CiteSpace, VOSviewer, and a bibliometric online analysis platform (https://bibliometric.com), which included the number of publications, citations, countries, institutions, journals, authors, references, and keywords. Results: 1,212 articles published in 201 journals from 65 countries were included in this study. The number of publications related to AS clinical trials is increasing annually. The United States and the Free University of Berlin, the countries and institutions, respectively, that have published the most articles on AS, have made outstanding contributions to this field. The author with the most published papers and co-citations over the period covered by the study was Desiree Van Der Heijde. The journal with the most published and cited articles was Annals of the Rheumatic Diseases. The keywords: "double-blind,” "rheumatoid arthritis,” "efficacy,” "placebo-controlled trial,” "infliximab,” "etanercept,” "psoriatic arthritis" and "therapy" represent the current research hotspots regarding AS. Discussion: This is the first study to perform a bibliometric analysis and visualization of AS clinical trial publications, providing a reliable research focus and direction for clinicians. Future studies in the field of AS clinical trials should focus on placebo-controlled trials of targeted therapeutic drugs.